2021
DOI: 10.1021/acsnano.1c03839
|View full text |Cite
|
Sign up to set email alerts
|

Non-Equilibrium Sodiation Pathway of CuSbS2

Abstract: Binary metal sulfides have been explored as sodium storage materials owing to their high theoretical capacity and high stable cyclability. Nevertheless, their relative high charge voltage and relatively low practical capacity make them less attractive as an anode material. To resolve the problem, addition of alloying elements is considerable. Copper antimony sulfide is investigated as a representative case. In this study, we do not only perform electrochemical characterization on CuSbS 2 , but also investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For the in situ TEM observation of sodium ion battery electrode materials, it was reported that metallic Na was generated from Na compound by electron beam irradiation and directly reacted with the active material. [16] In order to check such a beaminduced effect, the contact of both electrodes without applying voltage also has been carried out. In this case, no Li intercalation was observed.…”
Section: Resultsmentioning
confidence: 99%
“…For the in situ TEM observation of sodium ion battery electrode materials, it was reported that metallic Na was generated from Na compound by electron beam irradiation and directly reacted with the active material. [16] In order to check such a beaminduced effect, the contact of both electrodes without applying voltage also has been carried out. In this case, no Li intercalation was observed.…”
Section: Resultsmentioning
confidence: 99%
“…In the last century, a number of electrolytes for Cu-Sb alloy electrodeposition have been proposed to produce bright, corrosion-resistant hard alloys [3][4][5][6]. Recently, Cu-Sb-based alloys have been developed and investigated as a promising anodic material for Li-ion and Na-ion batteries, which have demonstrated high safety and capacity, as well as low weight and cost [4,[7][8][9][10][11]. Moreover, Cu-Sb-S and Cu-Sb-Se ternary semiconductors are considered as a sustainable alternative for fabricating lightabsorbing thin-film materials for solar applications owing to lower cell cost and recyclability [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As depicted in Figure 5f, when scanned from low voltage to high voltage (relative to Na/Na + ), at 0.1 mV s −1 , the SCN anode displayed four well-defined peaks of oxidation at 0.21, 0.29, 0.54, and 0.64 V, responding to the formation of Na 15 Sn 4 , Na 9 Sn 4 , NaSn, and NaSn 5 , respectively. 9,45,46 Furthermore, a pronounced reduction peak near 0.04 V, corresponding to the form of the Na x Sn alloy, can be observed as the voltage decreased. In addition, CV at sweep rates from 0.1 to 0.8 mV s −1 was performed to further study the behavior of Na + storage from 0.01 to 1.0 V (Figure 5f).…”
mentioning
confidence: 98%